On the Limits of Communication in Multidimensional Cheap Talk: A Comment - Levy, Gilat; Razin, Ronny (Econometrica, 2007)
We analyze a cheap talk game, à la Crawford and Sobel, in a multidimensional state and policy space. A feature of the multidimensional state space is that communication on one dimension often reveals information on others. We show how this feature imposes bounds on communication.